Synthesis, Characterization and Docking Study of Novel Pyrimidine Derivatives as Anticancer Agents - Manal Mohamed Talaat El-Saidi; Ahmed Ali El-Sayed; Erik Bjerregaard Pedersen; Mohamed Abdelhamid Tantawy; Nadia Ragab Mohamed; Wafaa Ahmed Gad (Indonesian Journal of Chemistry, 2020)
New compounds 5 and 9 using DNA bases e.g. Adenine 1 and Guanine 6 derivatives have been synthesized. The use of simple methods to synthesize compounds 5 and 9 were done using pyrimidine as an alternative DNA base ring. Another design to synthesize new simple pyrimidine rings utilizing thiourea and ethylcyano acetate to afford 6-amino-2-thiouracil was adopted. The reaction of thiouracil 10 with chloro cyano or chloro ester and ketone, resulted in the formation of adduct compounds 18-21, rather than the formation of compound 17. All the synthesized compounds were subjected to docking study, in order to gain insights into their binding modes against cyclin-dependent protein kinase 2 (CDK-2) that is involved heavily in cell cycle regulation and receptor protein B-cell lymphoma 2 (BCL-2) which is involved in cell apoptosis. These targets were selected based on their key roles in cancer progression via the regulation of the cell cycle and DNA replication. Molecular-docking analyses showed that compound 14e was the best docked ligand against both targets, as it displayed the lowest binding energy, critical hydrogen bonds and hydrophobic interactions with the targets.